Early detection and sensitive monitoring of CF lung disease: prospects of improved and safer imaging - Mall, Marcus A.; Stahl, Mirjam; Gräber, Simon Y.; Sommerburg, Olaf; Kauczor, Hans-Ulrich; Wielpütz, Mark Oliver (Pediatric pulmonology, 2016)
Recent imaging studies using chest computed tomography (CT) in presymptomatic infants and young children with cystic fibrosis (CF) diagnosed by newborn screening presented compelling evidence of early onset and progression of structural lung damage in CF. These data argue persuasively that non-invasive outcome measures for early detection and sensitive monitoring of lung disease applicable in the clinical setting will be instrumental for further improvement of clinical care and the development of early intervention therapies that have the potential to prevent irreversible lung damage. In this context, the use of CT imaging for early detection and long-term monitoring has the disadvantage of the risk to induce malignancies due to cumulating ionizing radiation exposure. More recently, magnetic resonance imaging (MRI) has emerged as an alternative radiation-free imaging technique for quantitative assessment of CF lung disease. In addition to structural lung damage, chest MRI enables non-invasive assessment of abnormalities in lung perfusion and ventilation characteristically associated with mucus plugging in CF lung disease. Here, we review recent developments and the prospects of MRI for improved and safer imaging with a focus on recent studies that support its utility as a sensitive non-invasive outcome measure of early lung disease in young children with CF. Pediatr Pulmonol. 2016;51:S49-S60. © 2016 Wiley Periodicals, Inc.
Gesehen am 06.05.2020